1995
DOI: 10.1071/zo9950059
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal-Variation in Water Flux, Field Metabolic-Rate and Food-Consumption of Free-Ranging Koalas (Phascolarctos-Cinereus)

Abstract: Mass-corrected field metabolic rates of free-ranging male koalas in central Queensland, Australia, varied between 0.329 MJ kg0.75 day-1 in summer and 0.382 MJ kg0.75 day-1 in winter. Field water influx measured 50.8 mL kg-0.8 day-1 in winter, increasing to 59.9 mL kg0.8 day-1 in summer for the same koalas, and was positively correlated with values for leaf moisture of food. Winter rates of water influx for koalas from Springsure were lower than those recorded for koalas from Victoria for the same period of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 0 publications
2
57
1
Order By: Relevance
“…These koalas (average mass males 6.7 kg; females Ellis et al Australian Zoologist volume 35 (2) 5 kg) range around the mine area, on the lease itself and on adjacent grazing, farming and undisturbed property and state forests. The results for winter (July) and summer (December) at Springsure, used for comparison, were as reported in an earlier study (Ellis et al 1995).…”
Section: Study Animalsmentioning
confidence: 99%
See 3 more Smart Citations
“…These koalas (average mass males 6.7 kg; females Ellis et al Australian Zoologist volume 35 (2) 5 kg) range around the mine area, on the lease itself and on adjacent grazing, farming and undisturbed property and state forests. The results for winter (July) and summer (December) at Springsure, used for comparison, were as reported in an earlier study (Ellis et al 1995).…”
Section: Study Animalsmentioning
confidence: 99%
“…The blood samples were collected in 5 ml sterile vials and frozen at -20 o C. These samples were then analysed as described by Ellis et al (1995).…”
Section: Analysis Of Water Turnover (Wtr) and Field Metabolic Rate (Fmr)mentioning
confidence: 99%
See 2 more Smart Citations
“…In subhumid central Queensland, annual records of water content in Eucalyptus foliage showed a trend that water concentrations were higher during summer, the rainy season (Ellis et al 1995). This study found that leaf moisture was significantly higher with the presence of surface water regardless of tree species.…”
Section: Impacts Of Water Availability On Koalas In Southwest Queenslandmentioning
confidence: 51%